Effect of Advertisement in Consumer Behavior - Manandhar, Binita (Management Dynamics, 2018)
This study is intended to analyze the impact of advertisement in consumer behavior. The purpose of this paper is to examine the impact of advertisement in consumer behavior. Convenience sampling is used for the study. All together 250 questionnaires were distributed to the customers from Kathmandu City and only 200 questionnaires were received. Most of the respondents have taken advertising as promotional tools that can convince the customers towards the products the study shows that the customers are highly affected by the advertisement as it creates curiosity on the customers and it provides information of the products, which is also important for the customers before buying any goods and services. So there is a positive impact of advertisement on consumer behavior. According to the respondents, television is more effective media to influence and convince the audience towards the advertised products.